Before and after photography. (1st October 2021) - Sweet, David
The challenge posed to nineteenth-century painting is placed in the context of current uncertainties about artificial intelligence. It is argued that at the centre of photography was an 'artificial retina', generating a highly unified pictoriality. Impressionism adopts this retinal or optical model. Before photography paintings were organized around perspective, allowing more spatial drama. However, perspective is also an example of artificial intelligence, based on eyesight. Cézanne disrupts the unity of Impressionism reintroducing elements of the pre-photographic, combining two scopic regimes. A feature of this hybrid approach is the diagonal, initially connecting the picture plane to the horizon, but modified in response to the photograph. This can be observed in many works from Cézanne to Matisse and beyond. Further examples of the function of this diagonal are discussed in reference to contemporary works by Tomma Abts, Sharon Hall and Marc Vaux.